A melting-pot for Pterodroma petrels on Rapa Nui: ecological divergence and reproductive isolation in a contact zone - Plaza, Paula; Cristofari, Robin; Gouin, Nicolas; Soto-Gamboa, Mauricio; Luna-Jorquera, Guillermo (Frontiers in Ecology and Evolution, 2023)
Speciation is thought to depend on general ecological segregation rather than on strict allopatry in species with planetary-scale foraging ranges, such as Pterodroma petrels. Separation in both breeding islands and foraging grounds are generally considered to be the conditions for prezygotic isolation. However, it is unclear how both can be maintained in a context of ongoing distributional range shifts due to global change, with range contractions and expansions caused by changing land use in breeding territories and oceanographic conditions impacting productivity areas. In this context, we expect that wherever the fragile balance of allopatric segregation breaks down, gene flow may be re-established across the borders of what is currently considered separated species. In these "melting pot" areas, fine-scale ecological differentiation is likely the only force opposing panmixia in otherwise highly similar organisms. In this study, we focus on six Polynesian Pterodroma species currently found on Motu Nui, a protected islet offshore of Rapa Nui (Easter Island), four of which have likely extended their breeding range to that island recently. To understand the fine-scale interaction between these closely-related species in their new contact zone, we used an integrative approach combining ecological and genetic methods, including morphometric, bioacoustics, stable isotope niche reconstruction, breeding site characterisation, phenology traits, and both nuclear and mitochondrial DNA markers. We found that significant amounts of gene flow occur across what is currently considered species boundaries, sometimes questioning the relevance of the accepted species classification. Interestingly, our results indicate that multivariate ecological distance between individuals in a group of closely related species (P. alba, P. atrata, P. heraldica, and P. neglecta) is a relevant predictor of gene flow intensity, while more distant species such as P. ultima and P. nigripennis seem to maintain reproductive isolation. Thus, the case of Pterodroma petrels supports the idea that incomplete allopatric speciation processes may be halted or even reversed on a secondary contact zone. Beyond their direct taxonomical relevance, our results underline the importance of considering fine ecological structures for biodiversity mapping and conservation policies.